Reasons for consultation and clinic constructivista - Rodríguez Charry, Diana M.; Universidad Santo Tomás, Colombia (Universidad Santo Tomás, Colombia, 2007)
The present article presents a framework of reflection for the action, on the consultation motives notion, little studied and nevertheless crucial for the definition of the process of consulting. It to seem that, originally, a lot of this is made since a medical framework of the disciplines, where the consultation is submitted to expert judgment of the consulted and with it the application would suffice of the to know about the expert on the patient, where the referring of study are the analysis of symptoms and antecedents with diagnostic goals. Nevertheless in social and human sciences, and particularly since a constructivist and complex position, is pertinent to redefine the notion and its comprehension, carrying out an ecological reading that imply the observer to realize the devices which builds maps of comprehension for the action. This initial work is called here clinical constructivist and the principles that orient it are outlined. With that, the position and responsibility of the consultants and consulted is valued, and the possible ways to work in the initial study of the motive of consultation are analysed. Key words: Reasons for consultation, consulting, clinical, constructivism and ecology.